SOVEREIGN INVESTMENT FUNDS, OPPORTUNITY WITHIN THE CONTEXT OF THE GLOBAL ECONOMIC CRISIS - Doina DRĂNICEANU, PhD Candidate (Financial Studies, 2013)
Emergent countries’ governments which have at their disposal huge amounts of money from external balances of trade strongly in excess became foreground investors, influential players on the financial markets by means of sovereign funds, often with political component. The economic crisis triggered in 2008 made the sovereign investment funds to adopt an active position in the financial markets, contributing through their massive interventions in the European and American banks, to the rescue of world economy, consolidating their position within the global financial sector. The consequences of the sovereign investment funds’ strengthening are both economic and political, influencing the pregnant change within the world power ratios in the new multi-polar world, from political and military point of view, with significant growth of interdependence of national economies.